Study the causes of delays in the country's development with Mathematical models - LILIANOU, Lisatteur; PHANALASY, Oudone; POYEYA, Souchanda (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
In this research, we study the causes of delays in the country's development delays by mathematical modeling. The data used in this study is the primary data obtained from the questionnaires with 300 students in the academic year 2020-2021 from the Faculty of Natural Sciences, National University of Laos. We apply two main methods for analyzing: 1. Microsoft Excel is used for statistical data analysis. 2. MATLAB is used for mathematical model data analysis to find the priority causes of delays in the county’s development. The results of the research are as follows: 1. Communication -transportation factors which have the first important sub-factor being no domestic and international freight trains and followed by insufficient domestic and international flight services; 2. Project management factors which have the first important sub-factor being the management of government investment to infrastructure by hiring private companies that is not transparent and unreasonable and followed by the management of government taxes not meet the goal; 3. Consumer-Consumption factor has the main sub-factor being the insufficient number of products supply to the domestic and foreign market and followed by the purchase of Lao people with high-quality products that import from abroad; 4. Investment which has the first important sub-factor being an insufficient investment in industry and trade for production to meet the demands for the domestic market and exporting and followed by insufficient investment in scientific research; 5. Education factor has the first important sub-factor being the low quality of private educational institutions and the only small number of graduate students from this sector getting work and followed by people graduated general education are low quality. In general, the main factors that delay the development of Laos ordered from the most to least important are project management, education, domestic and foreign investment, consumption and transportation, respectively.